Nicht korrekte Aufgaben in dem Hilbertschen Raume für lineare Gleichungen mit nicht beschränkten linearen Operatoren - Kabaila, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. П. Кабайла. Некоторые задачи в гильбертовом пространстве для линейных уравнений с неорганиченными линейными операторами V. Kabaila. Nekorektiški uždaviniai Hilberto erdvėje teisinėms lygtims su neaprėžtais tiesiniais operatoriais